The push-out bond strength of three root canal materials used in primary teeth: in vitro study - Özer, Hazal; Abaklı İnci, Merve; Açar Tuzluca, Sevcihan (Frontiers in Dental Medicine, 2023)
The study aims to compare the bond strength of three primary tooth root canal filling materials to the root canal wall with a push-out test (Calplus, Diapaste, BIOfactor MTA). First, 30 primary central teeth were cut transversely using a water-cooled low-speed diamond saw vertical to the long axis to obtain 2 mm thick discs from the middle third of the roots. Next, the materials used were placed on dentin discs and kept in an incubator for 1 week at 37 °C and 100% humidity until the hardening mechanism of the root-canal sealer was completed. Finally, a vertical force was placed on each material from apical to coronal with a 0.75 mm diameter stainless steel cylindrical piston without contacting the root canal dentin. The data were analyzed using the SPSS 22.0 program and Mann-Whitney U test was used as a post hoc test. There was a statistically significant difference between the bonding values of different primary tooth root canal sealers to root canal dentin (p<0.05). Among the maximum binding values, the lowest measurement was in Calplus (0.43±0.28 MPa), and the highest measurement was in BIOfactor MTA (24.24±17.78 MPa) (p<0.05). BIOfactor MTA has a higher bonding value to root canal dentin than calcium hydroxide-based primary tooth canal sealers.